Removal of Cr (VI) from an aqueous solution using an activated carbon obtained from teakwood sawdust: Kinetics, equilibrium, and density functional theory calculations (2020)
Because of its acute toxicity and high mobility, the hexavalent chromium [Cr (VI)] found in wastewater is a risk to the environment. In this study, activated carbon was produced from teakwood sawdust, which was chemically modified using ZnCl2 (AT) as an efficient adsorbent for Cr (VI) removal from aqueous systems. Batch experiments were conducted to identify kinetic, diffusional, and equilibrium parameters. In addition, to better understand the adsorption process, computer calculations were conducted based on the density functional theory (DFT). A maximum adsorption capacity of 72.46 mg g-1 was achieved by adapting experimental data to the Langmuir isotherm model. Intraparticle diffusion was further identified through a three-dimensional diffusion model, which revealed that it was ruled by intraparticular diffusion based on surface diffusion, with surface diffusion coefficient (Ds) values ranging from 1.29 × 10-10 to 0.78 × 10-10 cm2 s-1. Finally, computational chemistry calculations and an FTIR analysis determined that oxygenated functional groups, lactone, semiquinone, phenols, and carboxylic acids were involved in the process of Cr (VI) adsorption on AT. Moreover, the main adsorption mechanisms were found to be complexation, electrostatic interaction, and reduction of Cr (VI) to Cr (III). © 2020 Elsevier Ltd.